2019
DOI: 10.20944/preprints201904.0240.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sarcopenia is Associated Cognitive Impairment Mainly Due to Slow Gait Speed: Results from the Korean Frailty and Aging Cohort Study (KFACS)

Abstract: Cognitive impairment and sarcopenia may share common risk factors and pathophysiological pathways. This study was performed to examine the association between impairments in specific cognitive domains and sarcopenia (and its defining components) in a large group of community-dwelling older adults. Cross-sectional analysis was performed on the baseline data of 3,014 adults aged 70–84 years enrolled in the Korean Frailty and Aging Cohort Study (KFACS). The final analysis included 1,887 adults underwent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
2
9
1
Order By: Relevance
“…Our ndings agree with the recommended AWGS19 cut-off for GS criteria, despite a different walk distance of 6m in AWGS19 and 8ft in the present study (11). Other studies also reported a GS of <1.0 m/s in sarcopenic older adults (34), and found greater dementia risk and poorer health outcomes in adults >80 years with GS of <1.0 m/s (35,36). However, GS cut-off recommendations varied according to sarcopenia-associated health outcomes, such as hospitalisation, falls, mortality, cognitive impairment (37).…”
Section: Discussionsupporting
confidence: 90%
“…Our ndings agree with the recommended AWGS19 cut-off for GS criteria, despite a different walk distance of 6m in AWGS19 and 8ft in the present study (11). Other studies also reported a GS of <1.0 m/s in sarcopenic older adults (34), and found greater dementia risk and poorer health outcomes in adults >80 years with GS of <1.0 m/s (35,36). However, GS cut-off recommendations varied according to sarcopenia-associated health outcomes, such as hospitalisation, falls, mortality, cognitive impairment (37).…”
Section: Discussionsupporting
confidence: 90%
“…Our ndings agree with the recommended AWGS19 cut-off for GS criteria, despite a different walk distance of 6m in AWGS19 and 8ft in the present study (11). Other studies also reported a GS of <1.0 m/s in sarcopenic older adults (34), and found greater dementia risk and poorer health outcomes in adults >80 years with GS of <1.0 m/s (35,36). However, GS cut-off recommendations varied according to sarcopenia-associated health outcomes, such as hospitalisation, falls, mortality, cognitive impairment (37).…”
Section: Discussionsupporting
confidence: 90%
“…Previous cross-sectional and longitudinal studies have been conducted to determine the relationship between sarcopenia and cognitive status, which have yielded inconsistent conclusions. [ 4 ] Our findings revealed no association between sarcopenia as previously defined and cognitive impairment, after adjusting for potential covariates. The results of the present study were consistent with available evidence from a French observational, prospective, multicenter cohort study of community-dwelling elderly women.…”
contrasting
confidence: 53%